Islamic Pedagogical Transformation to Improve Critical Thinking in the Era of Globalization - Sodikin Sodikin (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The transformation of Islamic pedagogy is an imperative for Islamic educational institutions to effectively adapt to the dynamics of contemporary science and technology. This study aims to analyze the forms and strategies of Islamic pedagogical transformation that are relevant in addressing the challenges of educational globalization. Employing a qualitative-descriptive approach, this research applies conceptual analysis to contemporary practices and modern Islamic pedagogical thought. The findings reveal that the transformation of Islamic pedagogy is grounded in four fundamental concepts: (1) strengthening critical thinking, (2) applying a multicultural approach, (3) enhancing digital literacy and technology-based da’wah, and (4) implementing Islamic values in addressing global social issues. The identified implementation strategies include: (1) improving the capacity of educators and institutions, (2) redesigning curricula based on global competencies, (3) applying innovative learning models, and (4) reforming Islamic educational policies and infrastructures. The integration of Islamic pedagogy within these four domains serves not only as an adaptive response to the forces of globalization but also as a reinforcement of the continuity of Islamic intellectual tradition that has evolved since the classical era. This study affirms that the revitalization of Islamic pedagogy that is inclusive, critical, and technology-oriented constitutes a fundamental basis for developing a sustainable Islamic educational civilization in the global era.